Strategi Marketing Public Relations dalam Memperkuat Brand Awareness Astra Daihatsu Melalui Instagram @astradaihatsupondokcabe - Neima Aulia; Indira Dwi Kusumawardani; Tria Patrianti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The use of social media in public relations practices has become urgent because organizations are required to build communicative and consistent relationships with the public. At Astra Daihatsu Pondok Cabe, the management of the Instagram account @astradaihatsupondokcabe is still not optimal, as seen from the dominance of internal content, the lack of customer-oriented content, and the irregularity of posts. This condition has the potential to weaken brand awareness, especially amid competition with similar competitors who are more active and consistent in utilizing Instagram as a marketing communication medium. This study aims to analyze the implementation of Astra Daihatsu Pondok Cabe's Marketing Public Relations strategy through push, pull, and pass strategies in strengthening brand awareness on Instagram. The results show that the push strategy is more dominant, while the pull and pass strategies have not been effective due to limited creativity, dependence on Head Office materials, and the absence of structured content planning. The implications of this research emphasize the need to form a social media team, strengthen digital competencies, develop sustainable content planning, and increase consumer-oriented approaches to support the effectiveness of MPR and strengthen brand awareness.